Subclinical ocular surface changes in children with newly diagnosed allergy - Baytaroğlu, Ata; Saka, Mesut (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate subclinical changes in the anterior segment of the eye in pediatric patients with newly diagnosed allergic rhinitis or dermatitis compared to healthy controls.MethodsThis case-control study included children aged 3–15 years diagnosed with allergic rhinitis, dermatitis, or asthma. The control group consisted of healthy children matched for age and sex without systemic or ocular allergies. The Ocular Surface Disease Index (OSDI) questionnaire was administered with parental assistance, particularly to younger children. Ocular surface parameters, keratorefractive values, and corneal topographies were evaluated.ResultsNo significant differences were observed between the groups in terms of refractive status (p = 0.55). The OSDI scores were higher in the allergy group (p = 0.044), although the values remained below clinically relevant thresholds. Meibomian gland atrophy was significantly greater (24.4% vs. 15.8%, p = 0.008), and non-invasive tear break-up time (NiBUT) was significantly shorter (8.4s vs. 10.7s, p = 0.004) in the allergy group.ConclusionSubclinical ocular surface changes, including increased meibomian gland atrophy and reduced tear stability, may occur in children with asymptomatic allergies. While these findings do not currently influence treatment, they highlight the need for longitudinal studies to evaluate the potential progression and inform future screening practices.